The Influence Of Motivation, Communication And Job Stress On Employees' Job Satisfaction At Glowing Parfumery During The Covid 19 Pandemic - Merdiayana Merdiayana; Hendri Dunan (International Journal of Economics, Business and Innovation Research, 2024)
The purpose of this research is to find out whether motivation, communication and work stress have an impact on employee job satisfaction during the COVID-19 pandemic. The sample of this research consisted of 34 employees of Glowing Perfumery. The sampling method is a saturated sampling technique or census method which surveys the entire population because the population is small or less than one hundred. Examples in this study. Data analysis techniques in this study used multiple linear tests, t tests, F tests, and coefficient of determination tests Based on the problems and processing of the research results, the following conclusions are drawn: (1) Motivation has a positive effect on job satisfaction at Glowing Perfumery. (2) Communication has a positive effect on job satisfaction at Glowing Perfumery. (3) Job stress has a positive effect on job satisfaction at Glowing Perfumery. (4) Motivation, communication and work stress simultaneously affect job satisfaction at Glowing Perfumery. Future researchers doing similar work suggest that future researchers can broaden the scope of the site, view more sources and references, and consider other variables that may affect job satisfaction.